The Adoption and Implementation of the International Public Sector Accounting Standards: The Levels of Adoption and Implementation of IPSAS by United Nations in Nairobi. - Whitefield, Aleg A. (Journal of Public Policy and Administration, 2016)
Purpose: The purpose of this study is to assess the Levels of Adoption and Implementation of IPSAS by United Nations in Nairobi. Methodology:The study used a mixed research design involving both descriptive and explanatory research designs to describe the state of affairs of the study variables as well as test the cause and effect relationships between variablesAccording to United Nations (UN) website, there are 13 United Nations agencies in Nairobi Kenya with a total of 540 accountants. The choice of accountants as a population is because they are the most knowledgeable users. The study units for this study werethe junior and senior accountants.The sampling units for the study were drawn from the 13 agencies in the UN team of Kenya. A sample size of 20% of the population was taken as the sample size. This yielded 108 accountants. Random sampling was done. A close ended questionnaire based on a likert scale was used to collect data. Data wasanalysed by use of descriptive and inferential statistics. Specifically, frequencies count and regression analysis results were generated using SPSS version 20. Results: Based on the results majority of the agencies have implemented IPSAS to a high level. This significant level of adoption may have been as a result of UN general assembly agreement and resolution to encourage the agencies to implement IPSAS The results were also confirmed by other results which revealed that majority of the agencies have already implemented between 51 and 75% of the IPSAS modules. Unique contribution to theory, practice and policy:The study recommended thatIPSAS adoption would be improved if IPSAS software developers and funding organizations took into consideration the cost of modules, cost of training and general cost of implementing the IPSAS modules. The study also validates the Contingency theory which means that one thing is dependent on other things, and for organizations to be effective, there must exist a "goodness of fit" between their structure and the conditions in their external environment.